Antiseptics and microcosm biofilm formation on titanium surfaces - Georgia VERARDI; Maximiliano Sérgio CENCI; Tamires Timm MASKE; Bruna WEBBER; Luciana Ruschel dos SANTOS (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract Oral rehabilitation with osseointegrated implants is a way to restore esthetics and masticatory function in edentulous patients, but bacterial colonization around the implants may lead to mucositis or peri-implantitis and consequent implant loss. Peri-implantitis is the main complication of oral rehabilitation with dental implants and, therefore, it is necessary to take into account the potential effects of antiseptics such as chlorhexidine (CHX), chloramine T (CHT), triclosan (TRI), and essential oils (EO) on bacterial adhesion and on biofilm formation. To assess the action of these substances, we used the microcosm technique, in which the oral environment and periodontal conditions are simulated in vitro on titanium discs with different surface treatments (smooth surface - SS, acid-etched smooth surface - AESS, sand-blasted surface - SBS, and sand-blasted and acid-etched surface - SBAES). Roughness measurements yielded the following results: SS: 0.47 µm, AESS: 0.43 µm, SB: 0.79 µm, and SBAES: 0.72 µm. There was statistical difference only between SBS and AESS. There was no statistical difference among antiseptic treatments. However, EO and CHT showed lower bacterial counts compared with the saline solution treatment (control group). Thus, the current gold standard (CHX) did not outperform CHT and EO, which were efficient in reducing the biofilm biomass compared with saline solution.